EFFECT OF E. COLI LPS AND LUGOL’S IODINE ON CONCEPTION RATE IN REPEAT BREEDER COWS WITH SUBCLINICAL ENDOMETRITIS - RAJU, F SEBASTIN; KANTHARAJ, S; MURUGAVEL, K; PERUMAL, S VENKATESA; ANTOINE, D (The Indian Journal of Animal Reproduction, 2023)
Forty-five repeat breeder cows positive for subclinical endometritis by white side test were divided randomly intothree groups. Group-I cows (LPS) were administered 100 μg of E. coli LPS in 30 ml sterile phosphate buffered salineintrauterine once at estrus. Group-II cows (LI) were administered 1% Lugol’s iodine in 30 ml of distilled water (LI).Group-III cows (Control) were administered 30 ml sterile PBS intrauterine once at estrus. Haematological parameterssuch as Hb, TLC and DLC were studied before initiation of treatment and on the subsequent estrus also. AI was donein the subsequent estrus in all the cows. Pregnancy verification was done 45th day post AI. The mean Hb levelsignificantly increased in LPS and LI groups in subsequent estrus. The TLC count significantly decreased in LPS andLI groups in subsequent estrus. There was significant increase in the mean lymphocyte count and significant decreasein neutrophil count in LPS group in subsequent estrus. There was significant decrease in monocyte count in LPS,control group and significant decrease in the eosinophil count in LI group in the subsequent estrus. The first serviceconception rate was 53.33%, 20.00 % and zero per cent for LPS, LI and control groups, respectively.
Keywords: Repeat breeder cows; E. coli LPS; Lugol’s iodine; Haematology; Conception rate